Problematic Use of Alcohol and Online Gaming as Coping Strategies During the COVID-19 Pandemic: A Mini Review - Xu, Shijie; Park, Minkyung; Kang, Ung Gu; Choi, Jung-Seok; Koo, Ja Wook (Frontiers in Psychiatry, 2021)
The COVID-19 (coronavirus disease 2019) pandemic has dramatically changed our daily lives and activities, including those originally intended to serve for leisure and pleasure. Drinking and online gaming became coping behaviors used to rescue ourselves from the stress and restricted lifestyle during the COVID-19 pandemic. However, frequent drinking and gaming can result in the pathological consequences of addiction. Those affected use the stimuli not to obtain pleasure, but rather to avoid the displeasure induced by stress and previous use, often unsuccessfully. This review aims to provide an overview of recent longitudinal cohort studies on alcohol and gaming use during the COVID-19 pandemic, as well as to analyze how the pandemic has affected alcohol and gaming use. There was a substantial risk of alcohol and online gaming overuse during the lockdown, which may depend on the pandemic’s duration or overuse patterns. Previous studies have shown that increased alcohol consumption and online gaming are associated with heightened stress and anxiety levels caused by social isolation/quarantine. Over time, frequent or excessive alcohol consumption and gaming could lead to an increased risk of more serious mental health problems. Every effort should be made to mitigate mental health problems and ensure adequate adaptation to these exceptional circumstances. Therefore, it would be helpful to encourage physical activity, social interaction, and collaboration to facilitate psychological and physical health.